Biosynthetic pathway for leukotrienes is stimulated by lipopolysaccharide and cytokines in pig endometrial stromal cells - Barbara Jana; Aneta Andronowska; Jarosław Całka; Aleksandra Mówińska (Scientific Reports)
Abstract An inflammatory response is related to different inflammatory mediators generated by immune and endometrial cells. The links between lipopolysaccharide (LPS), cytokines, and leukotrienes (LTs) in endometrial stromal cells remain unclear. This study aimed to examine the influence of LPS, tumor necrosis factor (TNF)-α, interleukin (IL)-1β, IL-4 and IL-10 on 5-lipooxygenase (5-LO), LTA4 hydrolase (LTAH) and LTC4 synthase (LTCS) mRNA and protein abundances, and LTB4 and cysteinyl (cys)-LTs release including LTC4, by the cultured pig endometrial stromal cells, as well as on cell viability. 24-hour exposure to LPS, TNF-α, IL-4 and IL-10 up-regulated 5-LO mRNA and protein abundances. LPS increased LTAH mRNA abundance, while TNF-α, IL-1β and IL-10 augmented LTAH mRNA and protein abundances. TNF-α and IL-4 increased LTCS mRNA and protein abundances. In addition, LTCS mRNA abundance was enhanced by LPS and IL-4, while LTCS protein abundance was increased by IL-1β. Cells responded to LPS, TNF-α, IL-1β and IL-10 with increased LTB4 release. TNF-α, IL-1β and IL-4 stimulated LTC4 release. Cys-LTs release was up-regulated by LPS, TNF-α, IL-1β and IL-4. All studied cytokines augmented cell viability. In summary, LPS, TNF-α, IL-1β, IL-4 and IL-10 are potential LTs immunomodulatory agents in endometrial stromal cells. These functional interactions could be one of the mechanisms responsible for local orchestrating events in inflamed and healthy endometrium.